Neutrino Emission from Magnetized Microquasar Jets - Theodoros Smponias; Odysseas Kosmas (Advances in High Energy Physics)
The hadronic jets in a microquasar stellar system are modeled with the relativistic hydrocode PLUTO. We focus on neutrino emission from such jets produced by fast proton (nonthermal) collisions on thermal ones within the hadronic jet. We adopt a semianalytical approximation for the description of the secondary particles produced from p-p collisions and develop appropriate algorithms using the aforementioned injected protons as input. As a concrete example, we consider the SS-433 X-ray binary system for which several observations have been made the last decades. In contrast to the preset distribution of the fast protons along the jet employed in our previous works, in the present paper, we simulated it by using a power-law fast proton distribution along the PLUTO hydrocode. This distribution gradually sweeps aside the surrounding winds, during the jet advance through the computational grid. As a first step, in the present work, the neutrino energy spectrum is extracted from the model jet, facilitating a range of potential dynamical simulations in currently interesting microquasar jet systems.